Formulación y evaluación de criterios para la modifiación topológica de redes de distribución de agua potable ante futuros escenarios de cambio en la demanda :Modalidad: uso de software (2017)
Population growth is one of the most challenging factors around the design, operation and renewal of Water Distribution Systems (WDS). Nowadays, cities are subjected to many dramatic changes that may disturb the performance and original approach of urban infrastructure; among these are the informal settlements (slums) and overcrowding phenomena, mainly found in cities of developing countries as Colombia. This research focuses on the definition of a new WDS rehabilitation criteria, Available Power, and its subsequent evaluation and comparison with the Specific Power criteria, previously developed in the Water Supply and Sewer Systems Research Center of Universidad de los Andes (CIACUA). Both criteria were assessed under different future demand scenarios in five study cases: two networks of different Colombian towns of less than 12000 inhabitants and three District Metering Areas (DMA) of main Colombian cities. To this end, based in the minimum pressure requirement, a pipe-to-pipe rehabilitation methodology was proposed and programmed in MATLAB with EPANET?s toolkit. Capital costs and some surrogate measures of networks reliability were taken into account to assess the rehabilitated networks, and its results were compared with OPUS optimal designs. Both criteria proved to be good benchmarks to improve the hydraulic performance in each rehabilitated network. Additionally, was found a great difference in the suitability of each criteria considering the topological and topographic complexity of different networks layouts.